PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SENI RUPA KELAS VII-1 SMPN 15 PADANG - ZAMZAMI MUKHRA, Drs. Abd. Hafiz, M.Pd, Drs. Suib Awrus, M.Pd (Serupa The Journal of Art Education, 2014)
In this study the purpose of the use of media images to improve student learning outcomes in Arts subjects. The use of media images in the learning process using action research (Classroom Action Research). This research was conducted through two cycles, each cycle consisting of two meetings. In addition, there are four stages of the research procedures, namely: planning, observation, implementation, and reflection.The study used research instrument observation sheet student activities, teacher activities, and tests student learning outcomes. Student learning results obtained through test scores theory and practice. Based on the analysis of student learning to get results, obtained in the first cycle students who complete 11 percent of people with 34.37% and average 70.19% of learning outcomes. While in the second cycle increased student learning outcomes with 28 students who completed the percentage of 90.62% and an average 81.89% of learning outcomes. So it can be concluded that the use of media images in the process of learning can improve student learning outcomes. Through the research that has been done to all the students are expected to further improve learning outcomes, then the subject teachers of art and culture in order to efficiently use media images that increases student learning outcomes.Kata Kunci : Media Gambar, Hasil Belajar, Mata Pelajaran Seni Rupa